Age, sex, and frailty modify the expression of common reference genes in skeletal muscle from ageing mice. (March 2023) - Mishra, Manish; Kane, Alice E.; Young, Alexander P.; Howlett, Susan E.
Abstract: Changes in gene expression with age are typically normalised to constitutively expressed reference genes (RGs). However, RG expression may be affected by age or overall health and most studies use only male animals. We investigated whether expression of common RGs (Gapdh, Gusb, Rplp0, B2m, Tubb5, Rpl7l1, Hprt, Rer1) was affected by age, sex and/or overall health (frailty index) in skeletal muscle from young (4-mos) and aged (25–26-mos) mice. Standard RG selection programs recommended Gapdh (RefFinder/Genorm/NormFinder) or Rpl7l1 (BestKeeper) without considering age and sex. Analysis of raw Cq values showed only Rplp0 was stable in both sexes at both ages. When qPCR data were normalised to Rplp0, age affected RG expression, especially in females. For example, Hprt expression declined with age (Hprt=9.8 ×10 -2 ± 4.7 ×10 -2 vs. 6.5 ×10 -3 ± 8.8 ×10 -4 ; mean±SEM), while Gusb expression increased (6.0 ×10 -4 ± 5.5 ×10 -5 vs. 1.7 ×10 -3 ± 3.1 ×10 -4 ; n = 5/group; p < 0.05). These effects were not seen in males. Tubb5 and Gapdh were not affected by age or sex when normalised to Rplp0. Similar results were seen with normalisation by Gapdh or the Rplp0/Gapdh pair. Interestingly, RG expression was graded not only by age but by frailty. These data demonstrate that age, sex, and frailty of animals must be carefully considered when selecting RGs to normalise mRNA abundance data. Highlights: Standard tools selected different reference gene orders without considering age/sex. Cq analysis showed that only Rplp0 was stable in males and females at both ages. Age affected reference gene expression mainly in females. Reference gene expression was also graded by the degree of frailty. Reference gene expression was modified by age in a sex- and frailty-specific manner.